Langues Baltiques, Langues Slave - Аніщенко, Л.; Биховець, Н.; Калинович, Л.; Пономаренко, В.; Тараненко, A. (Мовознавство, 2013)
Рецензія на книгу: Langues Baltiques, Langues Slave / Sous la direction de D. Petit, C. Le Feuvre et H. Menantaud
Paris : CNRS Editions, 2011,— 290 p.